Performance Evaluation of Pump Station of Main Outfall Drain in AL Nassiriyah City (Journal of Engineering, 2020)
The Main Outfall drain pumping station in Nassiriyah is an important part in operation  system of the Main Outfall Drain (MOD) where it reduces the water levels in the U/S area of its and converted through Syphon freely under the Euphrates, its consists of several parts: U/S Basin, Station Building which contains 12 pumps, and Head Basin with Syphon, This station suffers from high levels especially in D/S area due to the current situation which is represented by establishing of dyke with pipes on MOD which located at 24 km from D/S of pumping station and Al-Khamisiyah Canal which located at 2.3 km from the U/S of dyke which feeds(Al Hammar Marsh) during drought season, several scenarios were adopted in order to explore the hydraulic effect of the current situation on the water levels and the performance of the syphon pumping system. The hydraulic effect of current situation causes an increase in D/S levels from 0.75 to 1 m,0.37to0.6m in operating (1,2)pumps, and the highest lack of the performance equal to 9.87%,5.58%,3.62%,2.62 % in operating (1,2,3,4)pumps respectively with designed head and 8.55%,5.40%,3.11%,1.8% with non- designed head.